Radical Holdings? Student Newspaper Collections in Australian University Libraries and Archives. Issue 3 (2nd July 2020) - Lymn, Jessie; Jones, Tamara
ABSTRACT: University student newspapers have a long history across Australian university campuses of engaging with contemporary social and political issues, often reflecting a sentiment not represented in mainstream media publications. Student newspapers have a demonstrated engagement with radical thinking, dissent and political activism and are an important published record of historical discourses, contributing to a critically informed understanding of the society that produced them. This paper reports on a pilot survey of Australian university holdings of their student newspapers. Findings inform current and future student newspaper collection practices by university libraries and archives, including building ongoing relationships with editorial teams, and recommended improvements for access to this primary source material for future researchers.